Identification of potential crucial genes associated with early‐onset pre‐eclampsia via a microarray analysis. Issue 5 (May 2017) - Ma, Yifei; Lin, Hongmei; Zhang, Hong; Song, Xiu'e; Yang, Huili
Abstract: Aim: This study aimed to identify potential key genes related to early‐onset pre‐eclampsia (EOPET), and to obtain a better understanding of the molecular mechanisms of this disease. Methods: The microarray dataset GSE44711 was obtained from the Gene Expression Omnibus, including eight chorionic villi samples from EOPET placentas and eight normal controls. The differentially expressed genes (DEG) were identified using the LIMMA package, and their potential functions were predicted by Gene Ontology (GO) enrichment analysis. Furthermore, protein–protein interactions (PPI) were obtained from the STRING database, and the PPI network was visualized by Cytoscape software. Then, significant modules were screened out from the PPI network, and GO enrichment analysis for DEG in modules was performed. Also, the potential transcription factors (TF) regulating DEG in modules were predicted, and TF–DEG network was visualized by Cytoscape. Results: A total of 270 upregulated and 200 downregulated DEG were identified. A set of DEG was related to functions such as female pregnancy and hormone metabolic process (e.g. NGF ). In PPI network modules, some DEG (e.g. SERPINE1 and FN1 ) were significantly associated with anatomical structure morphogenesis, and some other DEG (e.g. GZMA ) were relevant to the immune system process. Furthermore, SERPINE1, NGF, and FN1 interacted with each other and were regulated by RELA . Conclusion: The DEG related to hormone metabolic process (e.g. NGF ), anatomical structure morphogenesis (e.g. SERPINE1 and FN1 ), and immune system process (e.g. GZMA ) are predicted to play significant roles in the progress of EOPET, which will be confirmed by experiments in future.